Final configuration files for umbrella sampling in "Characterizing the free-energy landscapes of DNA origamis" - Doye, J (University of Oxford, 2021)
Final configuration and topology files in oxDNA format for each umbrella sampling window of the three DNA nanotube systems investigated.